IRIS: Integrated Retinal Functionality in Image Sensors - Yin, Zihan; Kaiser, Md Abdullah-Al; Camara, Lamine Ousmane; Camarena, Mark; Parsa, Maryam; Jacob, Ajey; Schwartz, Gregory; Jaiswal, Akhilesh (Frontiers in Neuroscience, 2023)
Neuromorphic image sensors draw inspiration from the biological retina to implement visual computations in electronic hardware. Gain control in phototransduction and temporal differentiation at the first retinal synapse inspired the first generation of neuromorphic sensors, but processing in downstream retinal circuits, much of which has been discovered in the past decade, has not been implemented in image sensor technology. We present a technology-circuit co-design solution that implements two motion computations - object motion sensitivity and looming detection - at the retina's output that could have wide applications for vision-based decision-making in dynamic environments. Our simulations on Globalfoundries 22nm technology node show that the proposed retina-inspired circuits can be fabricated on image sensing platforms in existing semiconductor foundries by taking advantage of the recent advances in semiconductor chip stacking technology. Integrated Retinal Functionality in Image Sensors (IRIS) technology could drive advances in machine vision applications that demand energy-efficient and low-bandwidth real-time decision-making.